Stress engineering of multi-pass weld metal to enhance structural integrity - Ganguly, Supriyo; Sule, Jibrin; Yakubu, Mustapha Y. (Springer, 2016)
In multi-pass welding, the weld metal and the associated heat-affected zone are subjected to repeated thermal cycling from successive deposition of filler metals. The thermal straining results into multi-mode deformation of the weld metal which causes a variably distributed residual stress field through the thickness and across the weld of a multi-pass weldment. In addition to this, the as-welded fusion zone microstructure shows dendritic formation of grains and segregation of alloying element. This may result in formation of micro-corrosion cells and the problem would aggravate in case of highly alloyed materials. Local mechanical tensioning is an effective way of elimination of the weld tensile residual stress. It has been shown that application of cold rolling is capable not only of removing the residual stress, but depending on its magnitude it may also form beneficial compressive stress state. Multi-pass structural steel welds used as structural alloy in general engineering and structural applications. Such alloys are subjected to severe in-service degradation mechanisms e.g., corrosion and stress corrosion cracking. Welds and the locked-in residual stress in the welded area often initiate the defect which finally results in failure. In the present study, a multi-pass structural steel weld metal was first subjected to post-weld cold rolling which was followed by controlled heating by a fiber laser. Cold straining resulted in redistribution of the internal stress through the thickness and controlled laser processing helps in reforming of the grain structure. However, even with controlled laser, processing the residual stress is reinstated. Therefore, a strategy has been adopted to roll the metal post-laser processing so as to obtain a complete stress-free and recrystallized microstructure.
Keywords: Laser processing; Mechanical properties; Microstructure; Multi-pass welds; Residual stress rolling steel